Revision of the Myopa testacea Species-Group in the Palaearctic Region (Diptera: Conopidae) - Stuke, Jens-Hermann; Clements, David K. (Zootaxa, 2008)
The Myopa testacea Species-Group is revised. Seven valid species are considered to belong to this group, and an identification key to these is presented. The known distribution information is evaluated, and the sparse information available on the biology is summarised. Myopa clausseni sp. nov. and Myopa hirsuta sp. nov. (= Myopa strandi auct., nec Duda 1940) are described; Myopa arabica Macquart, 1850 is reinterpreted as a valid species (stat. rev.) and Myopa strandi Duda, 1940 is placed as a junior synonym of Myopa vicaria Walker, 1849 (syn. nov.).